Pengaruh Mutasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Kementerian Kependudukan Dan Pembangunan Keluarga - Wulansari, Desika Putri; Murniyati (CV Warnak Johanna Nusantara, 2025)
Human resources are an important asset in government agencies. Having quality human resources is the desire of every agency because it can easily help achieve agency goals. The purpose of this study is to see the influence of job transfers and the work environment on employee performance. The study used a quantitative approach by distributing questionnaires to employees of the Human Resources Bureau of the Ministry of Population and Family Development with a population and sample of 50 people and using a saturated sampling technique. Analyzed using the SPSS program version 27. The results of this study are the t-test shows a value of 0.150 greater than 0.05, which means that job transfers partially have no significant effect on employee performance. The t-test also shows a value of 0.022 smaller than 0.05, which means that the work environment partially has a significant effect on employee performance. The results of the f-test show a significance value of 0.036 smaller than 0.05, which means that job transfers and the work environment simultaneously have a significant effect on employee performance.